Investigation of formaldehyde ground concentration depending on the heightof pipein the small town borowa - Дмитруха, Т.І.; Маджд, С. М.; Петрусенко, В. П.; Павчелюк, А.О. (Science-based technologies, 2018)
In the article the calculation of the ground concentration of formaldehyde is performed depending on the height of the pollution source in the settlement, where a furniture plant is located, and also the analysis of its change is provided. It was shown that one of the most dangerous compounds emitted by plant is formaldehyde. It is emphasized that finished products are caused by the release of the toxicity of the carcinogenic gas - formaldehyde into the environment. It is shown that concentration of formaldehyde at the distance of 300 m from the source of emissions exceeds the maximum permissible concentration, which has a direct connection with the height of the pipe. It has been found that for the formation of the ground concentration within the limits of the maximum permissible, it is necessary to increase the height of the pipe emission of the source to 10 m. Recommendations for the reduction of the ground concentration of formaldehyde in the settlement are given.